2016
DOI: 10.15244/pjoes/61788
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Effects of Simulated Nitrogen Deposition on Leaf Functional Traits of Rhus Typhina

Abstract: The effects of anthropogenic nitrogen (N) deposition on successful plant invaders, particularly potential effects on their leaf functional traits, have stimulated considerable research interest. This study aims to gain insights into the leaf functional traits of the controversial invader Rhus typhina in the presence of a gradient of simulated N deposition (control, 0 g L ). Soil pH is decreased under the growth of R. typhina. The soil acidifi cation mediated by R. typhina may be due to the positive effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 35 publications
(68 reference statements)
6
31
0
Order By: Relevance
“…Soil pH values of the two plants decreased with increasing cover classes. Researchers have found that invasive plants induce soil acidification [42][43][44]. PCA results also revealed that soil pH were important in determining the RA of the two plants under high cover classes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Soil pH values of the two plants decreased with increasing cover classes. Researchers have found that invasive plants induce soil acidification [42][43][44]. PCA results also revealed that soil pH were important in determining the RA of the two plants under high cover classes.…”
Section: Discussionmentioning
confidence: 97%
“…Soil pH values and moisture were determined using a digital soil acidity-moisture meter (ZD instrument ZD-06, China) [41][42].…”
Section: Determining Plant Characteristics and Soil Physicochemical Pmentioning
confidence: 99%
“…In most agricultural soils, soil available N is sufficient for early growth of legumes prior to the establishment of an effective N 2 fixation system. The application of N fertilizer improved the growth of invasive grass weeds that respond to N availability [22,24]. However, some studies have shown that alfalfa needs supplemental N when it is grown on extremely low N soils (e.g., salinealkali and sandy soils with nitrate levels below 15 mg kg -1 or organic matter below 15 g kg -1 ), or under conditions that limit the N 2 fixation symbiosis (e.g., low temperature) [35].…”
Section: Effect Of N Fertilizer On Yield Of Alfalfa and Weedsmentioning
confidence: 99%
“…Applying N fertilizer to increase yield potential has been routine practice for many alfalfa growers [19]. Although applying more N helps achieve the desired yield [20][21], it also can increase the chances of invasive weed growth [22][23] and result in greater levels of environmental pollution [24].…”
mentioning
confidence: 99%
“…Leaf length is the maximum value along the large strengthened vein along the midline of a leaf, and leaf width is the maximum value perpendicular to the large strengthened vein along the midline of a leaf [17]. The leaf length and width of [18][19][20]. The plant biomass was measured using an electronic balance.…”
Section: Determining Plant Characteristics and Diversitymentioning
confidence: 99%